ANALISIS EFISIENSI PERBANKAN SYARIAH SELAMA KRISIS GLOBAL DI INDONESIA - Hanifah Rahmi; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study aims to find out and analyze the efficiency of sharia bank during the global crisis in Indonesia. The types of research used are descriptive and associative research and the data in this study is secondary data from 2007 to 2009 with documentation and library study from relevant institutions and agencies. The analysis data used is descriptive analysis and inductive analysis. In inductive analysis this study uses the DEA method with an intermediation approach that is output oriented.The results of this study show that (1) The average of sharia bank reaches a perfect level of efficiency (100%) during the global crisis; (2) There are differences in the results of efficiency using two different models, they are CRS and VRS model; (3) The average level of efficiency of sharia bank during 2007 to 2009 is increasing; (4) Based on the CRS and VRS model, only Muamalat bank, Permata sharia bank, and Cimb Niaga sharia bank have the best performance compared to other banks during the period of the global crisis